Prolonging parathyroid hormone analog action in vitro and in vivo through peptide lipidation - Jakob Höppner; Hiroshi Noda; Anju Krishnan Anitha; Ross W. Cheloha; Thomas Dean; Michael Bruce; Daniel J. Brooks; Michael Mannstadt; Mary L. Bouxsein; Samuel H. Gellman; Ashok Khatri; Harald Jüppner; et al. (Nature Communications)
Abstract Parathyroid hormone (PTH) analogs with improved actions in vivo could lead to optimized treatments for bone and mineral ion diseases. Rapid clearance from the circulation and short dwell times on the PTH receptor limit the efficacies of conventional PTH peptides currently in medical use. Here, we seek to enhance PTH peptide efficacy using two distinct peptide lipidation strategies. First, we append a lipid chain to the peptide’s C-terminus in a fashion to promote binding to serum albumin and hence prolong the peptide’s circulation half-life in vivo. Second, we append a lipid chain to a lysine side chain in a fashion designed to anchor the peptide to the cell membrane as the ligand is bound to the receptor and hence increase its dwell time on the receptor. We find that both strategies of lipidation can profoundly enhance the efficacy of PTH peptides in vitro and in mice. Our results could lead to the development of modified PTH analogs with optimized therapeutic utility.